Decreased photosynthesis in the erect panicle 3 (ep3) mutant of rice is associated with reduced stomatal conductance and attenuated guard cell development - Yu, Hongyang; Murchie, Erik H.; Gonzalez-Carranza, Zinnia H.; Pyke, Kevin A.; Roberts, Jeremy A. (Oxford University Press, 2015)
The ERECT PANICLE 3 gene of rice encodes a peptide that exhibits more than 50% sequence identity with the Arabidopsis F-box protein HAWAIIAN SKIRT (HWS). Ectopic expression of the Os02g15950 coding sequence, driven by the HWS (At3g61950) promoter, rescued the hws-1 flower phenotype in Arabidopsis confirming that EP3 is a functional orthologue of HWS. In addition to displaying an erect inflorescence phenotype, loss-of-function mutants of Os02g15950 exhibited a decrease in leaf photosynthetic capacity and stomatal conductance. Analysis of a range of physiological and anatomical features related to leaf photosynthesis revealed no alteration in Rubisco content and no notable changes in mesophyll size or arrangement. However, both ep3 mutant plants and transgenic lines that have a T-DNA insertion within the Os02g15950 (EP3) gene exhibit smaller stomatal guard cells compared with their wild-type controls. This anatomical characteristic may account for the observed decrease in leaf photosynthesis and provides evidence that EP3 plays a role in regulating stomatal guard cell development.